Eleanor, Ellatony, Ellencake, and Me - Rubin, C.M. (Columbus, Ohio Gingham Dog Press, 2003)
Eleanor has a problem. Everyone in her family thinks they have the perfect nickname for her.
K - 2
Keywords: Nicknames - Fiction